MEDIA KEWIRAUSAHAAN SEBAGAI UPAYA MENUMBUHKAN POTENSI ENTREPRENEURSHIP - Heny Kusdiyanti; Karkono Karkono; Sopingi Sopingi; Indra Febrianto; Robby Wijaya (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
The needs of students in growing the potential of entrepreneurship must adjust these needs individualized students themselves. Current circumstances show that entrepreneurial education is only textbook in nature without providing experiential learning to students. The current solution has not been able to accommodate the needs of students, especially in the era of industrial revolution 4.0. Teachers only as facilitators that become business simulation mentors further aggravate the problems in entrepreneurial education today. So there needs to be a solution that can provide experimental learning and increase teacher participation in fostering the entrepreneurial spirit of students. This research aims to develop gamification-based edukit learning media that will be implemented in high school students to develop students' entrepreneurial potential. This type of research is development research using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation) by using questionnaires to collect research data. Once implemented, this research succeeded in increasing students' interest in entrepreneurial education as a provision for the growth of entrepreneurship potential in shiva. This learning medium also succeeds in improving the activeness of teachers and students in the learning process that provides experimental learning to students. Collaboration between gamification models and edukit learning media in accordance with the needs of students' competencies in the current industrial revolution 4.0. Follow-up research is needed to be done that focuses on digitizing media developed without eliminating the activeness of teachers and students in learning.